The foreign exchange rate exposure of nations - Horst Entorf; Jochen Moebert; Katja Sonderhof (Technische Universität Darmstadt, Department of Law and Economics, 2006)
Following the well-known approach by Adler and Dumas (1984) we evaluate the foreign exchange rate exposure of nations. Results based on data from 27 countries show that national foreign exchange rate exposures are significantly related to the current balance variables of corresponding economies.
Keywords: G15; F31; 330; Exchange rate exposure; international trade; current balance; Wechselkursrisiko; Kapitalertrag; Börsenkurs; Handelsbilanz; Schätzung; Welt